Evaluation of the Biodiversity of The Kelabit Highlands, Sarawak - Das, Indraneil; Fatimah, Binti Abang; Cheksum, Tawan; Mustapha, Abd Rahman; Andrew Alex, anak Tuen; Sepiah, Muid; Mohd Tajuddin, Abdullah; Isa, Bin Ipor; Petrus, Bulan; Charlie Justin, Mergie Laman (Research & Innovation Management Centre (RIMC) , UNIMAS, 2005)
Reported herein are the preliminary results of an evaluation of the biota of Mount Murud, Sarawak’s highest mountain massif within the Kelabit Highlands. Supported by an IRPA grant, inventories, systematic and ecological studies of selected groups of plants and animals were conducted in an attempt to evaluate the biodiversity and compile baseline data of this montane region for the management and conservation of these vital resources. This study reveals several new records of montane endemics and distribution. Several species found are new records for Mt. Murud, being reported in the past only from Mt. Kinabalu, the Crocker Range massifs, Gunung Mulu and G. Api, and in the case of macromoths, Bukit Retak, Brunei. The colubrid snake Stoliczkia borneensi, the scincid lizard Brachymeles apus and the ranoid frogs Meristogenys whiteheadi and Rhacophorus angulirostris are among these new records. Well-known endemics among the butterflies, which are previously only known from Mt. Kinabalu, Mulu and the Crocker range massifs are now also known from the Kelabit Highlands. These are Ptychandra talboti, Parantica crowleyi, Delias ninus parthenia, Kaniska canace maniliana, and Eurema tominia nabalua. All these represent range extensions of over 1,000 km to the south-west. Several new species are reported for the first time for Mt Murud and these include the amphibians and reptiles, Pelophryne sp. 1, Pelophryne sp. 2, Polypedates sp., Megophrys sp. and Sphenomorphus sp., respectively. For scarcity of previous work in Mount Murud, a large number of unidentified specimens remain, including a number of species that do not readily fit into currently recognised species. These include representatives of all the biota. An overall impression of the flora and fauna of Mount Murud as compared to Mt Kinabalu is that it is reminiscent of that of the middle elevations of Mt. Kinabalu.